2021
DOI: 10.3389/fnins.2021.614412
|View full text |Cite
|
Sign up to set email alerts
|

Circuit Mechanisms of L-DOPA-Induced Dyskinesia (LID)

Abstract: L-DOPA is the criterion standard of treatment for Parkinson disease. Although it alleviates some of the Parkinsonian symptoms, long-term treatment induces L-DOPA–induced dyskinesia (LID). Several theoretical models including the firing rate model, the firing pattern model, and the ensemble model are proposed to explain the mechanisms of LID. The “firing rate model” proposes that decreasing the mean firing rates of the output nuclei of basal ganglia (BG) including the globus pallidus internal segment and substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 169 publications
(226 reference statements)
1
17
0
Order By: Relevance
“…Multiple lines of evidence indicated that cFos and FosB are vital transcription factors from the Fos family involved in the mechanisms of dyskinesia. 28,29 During post DA denervation, the levels of FosB explicitly increased in the striatal region of chronic L-DOPA-treated rats 28 and PD patients. 30 In line with observations of the previous investigators, our study also reported that mRNA expression of cFos and FosB were effectively upregulated in the ipsilateral region of the striatum of LID rats.…”
Section: Lid-induced Alteration In Brain 5-ht and Da Turnover In The ...mentioning
confidence: 99%
“…Multiple lines of evidence indicated that cFos and FosB are vital transcription factors from the Fos family involved in the mechanisms of dyskinesia. 28,29 During post DA denervation, the levels of FosB explicitly increased in the striatal region of chronic L-DOPA-treated rats 28 and PD patients. 30 In line with observations of the previous investigators, our study also reported that mRNA expression of cFos and FosB were effectively upregulated in the ipsilateral region of the striatum of LID rats.…”
Section: Lid-induced Alteration In Brain 5-ht and Da Turnover In The ...mentioning
confidence: 99%
“…The ocular dyskinesia symptoms of our case were relieved with amantadine, suggesting that the N-methyl-D-aspartic acid-type glutamate receptors may regulate related pathways. 31 Further positron emission tomography scanning with the of N-methyl-D-aspartic acid receptors could be helpful in supporting this hypothesis.…”
Section: Discussionmentioning
confidence: 95%
“…Such observations were in good agreement with our results that dyskinetic PD patients exhibited enhanced connectivity between left DN and right putamen during ON medication state with the presence of clinical dyskinesias, which heralded that peak-dose dyskinesia might result from a pathological interaction in the DN-putamen loop. As we know, the putamen was the most affected region by dopaminergic denervation with the progress of PD ( Kish et al, 1988 ), which was concurrently considered the central target in the pathogenesis of LID ( Yang et al, 2021 ). Herz et al (2014) observed that dyskinetic PD patients displayed significant overactivation of bilateral putamen after levodopa intake.…”
Section: Discussionmentioning
confidence: 99%
“…As we know, the putamen was the most affected region by dopaminergic denervation with the progress of PD (Kish et al, 1988), which was concurrently considered the central The significance of post-hoc t-tests was set at voxel-level p < 0.001, cluster-level p < 0.01, corrected by Gaussian random field; Positive t-value indicates the regions in which the former group had higher functional connectivity than the latter group. target in the pathogenesis of LID (Yang et al, 2021). Herz et al (2014) observed that dyskinetic PD patients displayed significant overactivation of bilateral putamen after levodopa intake.…”
Section: Discussionmentioning
confidence: 99%